Hyperglycemia and its associated factors among people living with HIV on dolutegravir-based antiretroviral therapy in Ethiopia: a cross-sectional study - Enyew Fenta Mengistu; Adane Adugna; Mamaru Getinet; Gashaw Azanaw Amare; Baye Ashenef; Gelagey Baye; Desalegn Abebaw; Zigale Hibstu Teffera; Habtamu Belew; Temesgen Baylie; Muluken Getinet Mekuriaw; Dagmawi Abiy Abate; et al. (Therapeutic Advances in Infectious Disease)
Background: In many low- and middle-income countries, including Ethiopia, dolutegravir (DTG)-based regimens are the preferred first-line regimens for people living with HIV (PLWH). However, there are concerns about hyperglycemia and, in certain circumstances, diabetes mellitus in individuals who have switched to DTG. Objective: To assess the prevalence and factors associated with hyperglycemia among PLWH on DTG-based antiretroviral therapy (ART). Design: An institutional-based cross-sectional study. Methods: The study was carried out from December 1, 2021 to February 30, 2022, and included 423 participants who were recruited via a simple random sampling technique. We enrolled PLWH aged 18 years or older who had been on DTG-based ART for more than 6 months. Data were collected by using an interviewer-administered structured questionnaire, medical card review, physical measurement, and biochemical measurements. Hyperglycemia was defined as a fasting blood glucose level ⩾110 mg/dl. Multivariable logistic regression was used to identify factors associated with hyperglycemia, using SPSS version 26.0 software. Variables with a p -value of <0.05 were considered statistically significant. Results: The prevalence of hyperglycemia among PLWH receiving DTG-based ART was 12.1% (95% CI: 9.2–15.1). Age (AOR = 1.04, 95% confidence interval (CI): 1–1.08, p  = 0.036), BMI (AOR = 1.09, 95% CI: 1.01–1.17, p  = 0.022), and triglyceride level (AOR = 2.44, 95% CI: 1.28–4.64, p  = 0.006) were significant predictors of hyperglycemia among PLWH on DTG-based ART. Conclusion: Overall, our study revealed a high prevalence of hyperglycemia (12.1%) among PLWH receiving DTG-based ART. Age, BMI, and triglyceride levels were significant predictors of hyperglycemia. These findings underscore the importance of monitoring blood glucose levels in PLWH receiving DTG-based ART, with a special emphasis on patients with advanced age, increased BMI, and increased triglyceride levels.